TAFA2 Induces Skeletal (Stromal) Stem Cell Migration Through Activation of Rac1‐p38 Signaling. (17th December 2018) - Jafari, Abbas; Isa, Adiba; Chen, Li; Ditzel, Nicholas; Zaher, Walid; Harkness, Linda; Johnsen, Hans E.; Abdallah, Basem M.; Clausen, Christian; Kassem, Moustapha
Abstract: Understanding the mechanisms regulating recruitment of human skeletal (stromal or mesenchymal) stem cells (hMSC) to sites of tissue injury is a prerequisite for their successful use in cell replacement therapy. Chemokine‐like protein TAFA2 is a recently discovered neurokine involved in neuronal cell migration and neurite outgrowth. Here, we demonstrate a possible role for TAFA2 in regulating recruitment of hMSC to bone fracture sites. TAFA2 increased the in vitro trans‐well migration and motility of hMSC in a dose‐dependent fashion and induced significant morphological changes including formation of lamellipodia as revealed by high‐content‐image analysis at single‐cell level. Mechanistic studies revealed that TAFA2 enhanced hMSC migration through activation of the Rac1‐p38 pathway. In addition, TAFA2 enhanced hMSC proliferation, whereas differentiation of hMSC toward osteoblast and adipocyte lineages was not altered. in vivo studies demonstrated transient upregulation of TAFA2 gene expression during the inflammatory phase of fracture healing in a closed femoral fracture model in mice, and a similar pattern was observed in serum levels of TAFA2 in patients after hip fracture. Finally, interleukin‐1β was found as an upstream regulator of TAFA2 expression. Our findings demonstrate that TAFA2 enhances hMSC migration and recruitment and thus is relevant for regenerative medicine applications. Stem Cells 2019;37:407–416 Abstract : During the inflammatory phase of fracture healing, elevated levels of interleukin‐1β induce TAFA2 production at the site of fracture, leading to recruitment of osteoprogenitor cells needed for subsequent bone formation.